DUALISM AND INTEGRATION SYSTEM OF EDUCATION: PERSPEKTIF SEJARAH - Ikhtiono, Gunawan (AKADEMIKA: Jurnal Pemikiran Islam, 2018)
Abstract A mosque was the first place to conduct education, from which science developed to experience its heyday in the 12th and 13th centuries AD. Methods of scientific discussions taking place within such as the As-Shofwah Brotherhood, Bait Al-Hikmah, Daarul Hikmah, were supported by the Caliphs or community leaders by giving maximum funding assistance. From the mosque, educational institutions developed into Madrasah Nidzamiyah to Al-Qarawiyyin University and Al-Azhar University. Nevertheless, such funding assistance is never free from political agenda aimed at developing and maintaining cetain ideals or schools of thought. As for the learning process, the sulthans and muslim scholars do not distinguish between the sciences related to the world and that related to the hereafter (habluminallah wa habluminannas). Both are studied and explored without separating them. So, in the golden age of Islam, an expert in the field of medicine could also be an expert in in the field of Sufism. An expert in worship might also be an expert in astronomy, and a mathematician could be a philosopher as well. Keywords: Mosque, Management, Curriculum, and Integration of Science Abstrak Masjid adalah tempat pertama yang menyelenggarakan pendidikan. Dari Masjid itu Ilmu Pengetahuan berkembang hingga mengalami masa kejayaannya di abad 12 dan 13 M. Metode diskusi-diskusi ilmiah yang berlangsung di dalamnya, seperti Ikhwan As-Shofwah, Bait Al-Hikmah, Daarul Hikmah, didukung oleh para Khalifah ataupun tokoh masyarakat dengan memberikan bantuan pembiayaan yang sebesar-besarnya. Dari Masjid itulah lembaga pendidikan berkembang menjadi Madrasah Nidzamiyah hingga Universitas Al-Qarawiyyin dan Universitas Al-Azhar. Meskipun demikian, tidak terelakkan bahwa bantuan-bantuan tersebut ada muatan politik untuk mengembangkan serta mempertahankan faham/mazhab yang anutnya. Adapun dalam proses pembelajarannya, para Sulthan dan para Cendikiawan Muslim tidak membedakan antara Ilmu yang berhubungan dengan dunia dan akhirat (habluminallah wa habluminannas). Keduanya dipelajari dan didalami tanpa memisahkannya. Sehingga, di zaman keemasan Islam (the golden age), seseorang yang ahli dalam bidang Kedokteran tetapi juga seorang yang ahli Tasawuf. Seorang yang ahli ibadah, adalah juga seorang yang ahli Astronomi. Seorang ahli Matematika juga sebagai Filosof. Kata Kunci: Masjid, Manajemen, Kurikulum, and Integrasi Keilmuan